THE EFFECT OF THE ADDITION RED SPINACH FLOUR (Amaranthus tricolor L) ON THECONSUMER ACCEPTANCE TO REBON SHRIMP MACARONI (Acetes sp.) - Risky Amalia; Suparmi Suparmi; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aimed to observe the effect of addition of red spinach flour on the consumer acceptance torebon shrimp macaroni and to determine the best formulation for red spinach addition, so that it can be used as a natural color in rebon shrimp macaroni products. This research was conducted in August-September 2020 at the Laboratory of Fisheries Product Technology and Chemical Laboratory of Fisheries Products, Faculty of Fisheries and Marine, at the Riau University Pekanbaru. The method used was an experimental with 4 levels of treatment for the addition of red spinach flour, namely: 0 g (control), 100 gs, 200 gs, and 300 gs, and repeated 3 times. The parameters observed were organoleptic tests includes appearance, odor, texture and taste. Furthermore,the proximate test includes moisture, protein, fat, and ash content. The results showed that the addition of 100 gs of red spinach flour was the best treatment, indicated by the highest consumer acceptance rate of 91.56%, and characterized by slightly spinach tasted. The product was containing moisture of 9.98%, an ash of 1.57%, a fat of 0.13% and a protein of 12.67%. Keywords: Macaroni, rebon shrimp, red spinach flour